Unique position of a pancreatic head insulinoma during laparoscopic enucleation: case report - Alshamrani, Abdullah M.; Ghabbani, Hisham M.; Alobaid, Omar M.; AlShehri, Abdullah J.; Alzaraa, Khalid M.; Alshurafa, Haider A. (International Surgery Journal, 2020)
Insulinomas are benign pancreatic neuroendocrine tumors that require surgical intervention as a therapeutic measure. We describe an 18-year-old male patient who presented to the emergency department with a history of syncope, blurred vision, and diaphoresis. His blood sugar level was low upon admission, and a 72-hour fasting plasma glucose test showed low serum glucose, high serum insulin, and high C-peptide. An abdominal computed tomography scan and magnetic resonant imaging revealed a solitary tumor in the pancreatic head with no sign of ductal dilatation. Laparoscopic enucleation was performed, and a histopathological examination revealed findings consistent with insulinoma. The patient’s postoperative course was uneventful, and his follow-up examination was unremarkable. In conclusion, physicians should have a high clinical suspicion index for insulinomas, especially in young patients with a history of syncope, blurred vision, and diaphoresis, in order to avoid delayed diagnosis.